Image's travel - Prata, Didiana (Revelar: Revista de Estudos da Fotografia e Imagem, 2018)
This article deals with the 'grand tour' of indexed images on social networks and of new contexts and functions of images potentialized by the media in which they are produced, edited and published. In light of database aesthetics - a great change in paradigm in which the use of metadata information is central in the onfiguration, visualization and design of the narrative - we will talk about the nature of this digital and numerical image in constant transformation and how images travel on networks. Lastly, we will analyze the singularities of the 'grand tour' of mobile images, and their potentiality as travelling images (transits and rajectories), greater and more infinite than their author's journey. As an iconographic reference, we will use and edit representative images of Siio Paulo's landscape on Instagram, conducted by the author (Prata, 2016).